2019
DOI: 10.1039/c9cc01678c
|View full text |Cite
|
Sign up to set email alerts
|

Strong CPL of achiral AIE-active dyes induced by supramolecular self-assembly in chiral nematic liquid crystals (AIE-N*-LCs)

Abstract: AIE-N*-LCs prepared by supramolecular self-assembly between achiral AIE-active dyes and N*-LCs can exhibit highly strong CPL signals with gem values in the range from 0.97 to 1.42. Most importantly, their emission wavelength can be tuned by changing the AIE-active dye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(76 citation statements)
references
References 54 publications
2
73
0
1
Order By: Relevance
“…Aggregation‐induced emission (AIE) is a phenomenon that the luminogens which are non‐emissive at a molecular state, are induced to show strong emission under aggregation. The aggregation induced CPL (AICPL) of the AIEgens has been well investigated. However, the CPL of segregated AIEgens was rarely reported .…”
Section: Methodsmentioning
confidence: 99%
“…Aggregation‐induced emission (AIE) is a phenomenon that the luminogens which are non‐emissive at a molecular state, are induced to show strong emission under aggregation. The aggregation induced CPL (AICPL) of the AIEgens has been well investigated. However, the CPL of segregated AIEgens was rarely reported .…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting here that significant enhancement of g lum could be observed occasionally in nano-assemblies or in aggregated systems as a result of the formation of chiral microstructural materials or films (Geng et al, 2003 ; Kumar et al, 2015 ; Roose et al, 2016 ; Sang et al, 2019 ), in particular for few electroluminescent systems, such as OLEDs (Brandt et al, 2016 ; Song F. et al, 2018 ). In addition, the incorporation of emissive moieties into anisotropic media, such as chiral liquid crystals displaying helical macrostructures, proved to be an efficient strategy for the generation of strong CPL emission (Watanabe and Akagi, 2014 ; Goto, 2018 ; Gao et al, 2019 ; Kim et al, 2019 ; Li et al, 2019 ; Yang X. et al, 2019 ). Focusing on isotropic solutions, some recent up-converted CPL studies evidenced enhanced g lum compared to their downshifted counterparts.…”
Section: Physical Basis Of Cpl and Strategies To Achieve Strong Cpl Ementioning
confidence: 99%
“…But so far there have been very few works on CPL‐active N*‐LCs materials. [ 33–35 ] Recently, Ikai's group reported that the helical supramolecular polymers were assembled as a cholesteric liquid crystal, strong chiral amplification effect, and intense CPL signal ( g em = 1.0 × 10 −2 ) were observed while adding infinitesimal achiral dyes into cholesteric LC to form N*‐LCs. [ 36 ] In 2019, Duan and co‐workers explored a new pathway to develop the novel CPL‐active LC material by dispersing chiral emitters and a triplet donor into N‐LCs, the g em of N*‐LCs could be amplified one order of magnitude up to about 0.04 through remarkable photon upconverted circularly polarized luminescence (UC‐CPL) mechanism.…”
Section: Methodsmentioning
confidence: 99%